Impact of nitrogen on the charge-to-spin conversion efficiency in antiferromagnetic Mn3PtN compared to Mn3Pt thin films - Tripathi N.; Mishra S.K.; Miura Y.; Isogami S. (My University, 2025)
The bilayer structures consisting of Mn3PtN (5 nm)/CoFeB(3 nm) and Mn3Pt(5 nm)/CoFeB(3 nm) were fabricated via magnetron sputtering to investigate the role of nitrogen on charge-to-spin conversion efficiency in the noncollinear antiferromagnets (AFMs). The crystal structure of Mn3PtN (MPN) without N is consistent with that of Mn3Pt (MP) with L12-ordered structure, which allows us to study the different charge-to-spin conversion efficiency for AFMs with and without N. The spin-torque ferromagnetic resonance and second-harmonic Hall measurements were performed for both samples. It was revealed that the spin Hall angle (θSH) of the MPN with spin polarization in the y direction was observed to be ∼0.033, exceeding the corresponding value of MP (∼0.025), which was qualitatively supported by the first-principles calculation. These results led us to conclude that N plays a crucial role in stabilizing the noncolliear antiferromagnetic structure and creating an electronic state advantage for the enhanced θSH. © 2024 American Physical Society.